ASSOCIATION BETWEEN OCCUPATIONAL NOISE EXPOSURE AND HYPERTENSION RISK: META ANALYSIS - Aurina Firda Kusuma Wardani; Siti Rachmawati; Anggreini Beta Citra Dewi (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Noise is a common occupational physical hazard that, when esposure exceeds threshold limits, can elevate blood pressure. Work-related hypertension may affect workers’ productivity. Purpose: To conduct meta-analysis of the association between occupational noise exposure and the risk of high blood pressure. Review: The authors performed meta-analysis of 10 articles published between 2018-2023 from different sources, including Google Scholar, PubMed, and Science Direct. The terms